PEMANFAATAN ALAT PERMAINAN EDUKATIF ULAR TANGGA DALAM PENERAPAN PEMBELAJARAN TEMATIK DI KELAS III SD - Aini Indriasih (Jurnal Pendidikan, 2015)
Games as tools in education is one of the media-based simulation designed to stimulate the existing problems, in order to obtain the essence of science that can be used to solve the problem. This research was conducted with the purpose of implementing the thematic-based character education by utilizing the tools of educational games. The results of this study are expected to provide an alternative activity to play in learning process and cultivate children to skillfully handle the problem independently, encouraging teachers to be more creative in educating the children with media interest and in accordance with the children's development. This study used a quasi-experimental design. The data collection technique used was the test and observation guidelines. Implementation of research had been done in class III SD 02 Temulus in Distric of Kudus in central of Java. The research result showed that the activity of students in the learning was 84 which is very active. The result of learning process skills was 81, while learning completeness score was 88. The test results influenced the activity of the students’ learning as big as 0,684. There was still 0,352 of variance which was influenced by other variables. The influence of skills in the learning process of students to the students test scores was 0,616. It means, there are other variables which influence the test scores as big as 0,384. Comparative tests between pre-test and post-test (t test) was t = 12,2*, means that there was difference in learning outcomes before and after treatment. Alat permainan edukasi adalah salah satu media berbasis simulasi didesain untuk menstimulasikan permasalahan yang ada, sehingga diperoleh esensi ilmu yang dapat digunakan untuk menyelesaikan masalah.Penelitian ini dilakukan dengan tujuan menerapkan pendidikan karakter berbasis tematik dengan memanfaatkan alat permainan edukatif. Hasil penelitian ini diharapkan dapat memberikan alternatif kegiatan bermain sambil belajar dan membudayakan anak untuk terampil mengatasi masalahnya secara mandiri, mendorong guru untuk dapat lebih kreatif membelajarkan anak dengan media yang menarik dan sesuai dengan perkembangan anak. Penelitian ini menggunakan desain quasi eksperimen (eksperimen semu). Sedangkan teknik pengumpulan yang digunakan adalah tes dan pedoman observasi. Pelaksanaan penelitian dilakukan di kelas III SD02 TemulusKabupaten Kudus. Dari hasil penelitian diperoleh nilai keaktifan siswa dalam pembelajaran sebesar 84 dengan kriteria sangat aktif. Adapun nilai keterampilan proses dalam pembelajaran sebesar 81 dengan kriteria terampil, sedangkan ketuntasan belajar diperoleh skor 88. Dari hasil uji pengaruh keaktifan terhadap hasil belajar diperoleh skor 0,684 yang artinya masih ada pengaruh dari variabel lain sebesar 0,352. Sedangkan pengaruh keterampilan proses siswa dalam pembelajaran diperoleh skor 0,616 sehingga masih ada pengaruh variabel lain sebesar 0,384. Uji banding sebelum dan sesudah perlakukan (uji t) diperoleh nilai t = 12,2 < 0,05 dapat diartikan bahwa ada perbedaan hasil belajar sebelum dan sesudah perlakuan.